A Study on Magnetoresistivity, Activation Energy, Irreversibility and Upper Critical Field of Slightly Mn Added Bi-2223 Superconductor Ceramics - Dogruer, M.; Zalaoglu, Y.; Varilci, A.; Terzioglu, C.; Yildirim, G.; Ozturk, O. (Springer Science and Business Media LLC, 2012)
This study discusses the effect of Mn addition on the superconducting and physical properties in Bi1.8Pb0.4Sr2Mn x Ca2.2Cu3.0O y bulk superconductors with x=0,0.03,0.06,0.15,0.3, and 0.6 by means of the magnetoresistivity measurements. The magnetoresistivity of the samples prepared using the standard solid-state reaction method was measured for different values of the applied magnetic field strengths. The superconducting and physical properties of the samples such as the zero resistivity transition temperatures (T c ), irreversibility fields (μ 0 H irr ), and upper critical fields (μ 0 H c2) were deduced from the magnetoresistivity curves. Moreover, thermally activated flux creep model was studied for activation energy (U 0) values of the samples. According to the results of the measurements, not only were the T c and U 0 values of the samples found to decrease significantly but the μ 0 H irr and μ 0 H c2 values were also observed to reduce with the increase in the Mn addition, indicating that the doping degrades the physical and superconducting properties of the samples.
Keywords: Bi-1.8Pb0.4Sr2MnxCa2.2Cu3.0Oy; Magnetoresistivity; Activation Energy; Irreversibility Field; Upper Critical Field; 7. Clean energy